Temporal shifts in the collective dermatologic microbiome of military trainees - Gibbons TF; Noe JC; Patterson AT; Lenz BL; Beachkofsky TM (Dove Medical Press, 2019)
Thomas F Gibbons,1 Jody C Noe,1 Andrew T Patterson,2 Brittany L Lenz,2 Thomas M Beachkofsky3159th Medical Wing Science and Technology, Clinical Investigations and Research Support, San Antonio, TX, USA; 2Department of Dermatology, 59th Medical Wing, San Antonio, TX, USA; 3Department of Dermatology, 6th Medical Group, Tampa, FL, USACorrespondence: Thomas M BeachkofskyDepartment of Dermatology, MacDill AFB, Tampa, FL 33621, USATel +1 813 827 9379Email thomas.m.beachkofsky.mil@mail.milBackground: New military members undergo a highly-regimented 7-week training course during which trainees live and work within the same group of approximately 50 subjects for nearly 24 hours a day. This creates an optimal environment for assessing the impact of communal living on the collective skin microbiome.Purpose: The objective of this pilot study was to investigate dynamic changes of the skin microbiome in basic military trainees (BMT), in light of the unique environmental influences faced by this population.Patients and methods: We evaluated collective changes in the skin microbiome of normal healthy adult basic trainees in response to communal living and universal Group A Strep prophylaxis with penicillin over the course of their initial 7-week training course. Samples from 10 flights of trainees were collected by swabbing upon arrival at Lackland AFB for their training (week 0) which is prior to prophylaxis with penicillin, at the 4 week point, and at the conclusion of their 7-week course of basic military training. Three separate high-throughput sequencing platforms and three bioinformatic pipeline analysis tools were utilized to assess the data.Results: At all three time points we found that the top three bacterial genus identified were Propionibacterium, Staphylococcus, and Corynebacterium. We detected a community membership difference between the initial week 0 samples and the week 4 and 7 samples. A strong inverse correlation between Propionibacterium and Staphylococcus was noted with Propionibacterium being high at week 0 and much lower at weeks 4 and 7; conversely, Staphylococcus was low at week 0 and higher at weeks 4 and 7, this relationship was noted in both the individual and collective specimens.Conclusion: The collective dermatologic microbiome in the military trainee population examined exhibited a relative increase in Staphylococcus and Corynebacterium abundance coupled with a relative decrease in Propionibacterium abundance in this observational pilot study. Additional studies are needed to further assess the causal impact of communal living and widespread penicillin chemoprophylaxis.Keywords: metagenomics, 16S rRNA, prophylaxis, bacteria, penicillin